ANALYSIS OF FISH PROTEIN CHANGES DURING PROCESSING WITH SALT - Alimurrahman Alimurrahman; Mohammad Taufiq Hidayat; Doni Ferdiansyah (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2021)
Indonesia So far, there has been no study regarding the effect of the stages of traditional fish processing in Indonesia on changes in the molecular weight profile and allergenicity. The objectives of this study were (1) to obtain a molecular weight profile of fish protein extracts during the salted fish processing stage of the five types of marine fish that were mostly produced in P3 Pasongsongan; (2) obtain the level of allergenicity of fish protein extracts during the salted fish processing stage of the five types of fish tested; and (3) obtain information on changes in the allergenicity of similar marine fish protein extracts due to the application of salted fish and pindang fish processing technology. In the first stage, secondary data was collected to obtain information on the five types of salted fish that were most widely produced in P3 Pasongsongan which would then be selected as samples. In addition, observations and interviews were also conducted with 25 salted fish producers in P3 Pasongsongan to obtain a profile of salted fish processing that will be used as a standard for sample processing. SDS-PAGE electrophoresis test showed that the processing of salted and pindang fish could not remove the protein bands thought to be parvalbumin (10 to 13 kDa) and other polypeptides suspected to be major allergens in fish (24, 40, and 50 kDa). Potential allergenicity of wet salted fish from the highest to the lowest, namely tuna > mackerel > selar > kite > tembang. Allergenicity potential of dried salted fish from the highest to the lowest, namely layang fish > tembang > tuna > mackerel > selar. Fried salted fish has the highest allergy potential, while mackerel and fried salted tuna have the lowest allergy potential. Comparison of the allergenicity test results for mackerel during the processing stages of salted fish and pindang fish showed that the allergenicity of mackerel processed with salting was higher than that of mackerel processed with salting.